Multilingual practices in Norwegian-German family conversations from the perspective of conversational analysis - Elstrand, Kristin Børde (Målbryting, 2025)
This article shows how Norwegian-German adolescents negotiate the framework of participation in family conversations by combining code-switching with multimodal resources. The data consists of self-made video recordings of everyday conversations from two multilingual families (13 recordings, approx. 4 hours), recorded between December 2022 to January 2023. Both families have children of adolescent age (between 15 to 20 years) who have had their upbringing in Norway, whereas their parents moved to Norway from Germany as adults. Through detailed analyses of authentic conversations, based on Auer’s (1995) theories on code-switching, the material shows that the adolescents use code-switching, in combination with multimodal resources, to suggest changes in the participant framework within the family conversation. This often occurs when there are disagreements between the adolescents in the family interactions. The results show how codeswitching can contextualize both a participant’s preferred language and the changes that occur within the conversation’s structure at the same time. The analysis employs multimodal conversation analysis to deepen the present understanding of multilingual adolescents’ linguistic practices in family conversations, as offered by existing sociolinguistic studies. Thus, the article provides insight into how code-switching is a resource in the interaction between multilingual participants, and it shows how the term of code-switching may be a useful and important tool when studying multilingual conversations.
Keywords: conversation analysis; multilingualism; family interaction; adolescents; code-switching; participation framework; multimodality